Utilization Of Online Quizizz For Arabic Language Learning - Rezi, Melisa; Mudinillah, Adam; Putri, Lusiana Rahmadani; Shidqi, Muhammad Husni (Ijaz Arabi Journal of Arabic Learning, 2023)
Students who experience problems when carrying out learning cannot come to school for a certain reason, cannot receive learning material and cannot carry out learning on that day. That is because the difficulties of students in understanding learning make students less understanding of the lesson, due to a lack of innovation in learning at school. This study aims to increase enthusiasm for learning Arabic by using the use of the Quizizz application. The method used by researchers is a quantitative method, this quantitative research can show data containing numbers that can be obtained by using Google from as a means to create a questionnaire that researchers can use as subjects of their research. Improving the learning quality of students in utilizing the use of Quizizz in learning Arabic is one of the results to be proud of. The conclusion from this study is that the quizizz application can increase students' enthusiasm for learning and can test students' abilities. The limitations of this study are that the researcher only conducted research at one institution, the researcher hopes that there will be similar research, but in different learning besides learning Arabic so that it can increase the reader's understanding of the issues that will be examined later. This study also recommends future research to make it a challenge in utilizing the use of Quizizz in learning Arabic.